Adult Patients Da Immunological Aspects of Diagnosed Chronic Kidney Disease (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
clinical immunology in various pathological conditions, as well as in patients diagnosed with chronic kidney disease (CKD), provides information about the state of the immune system , changes in the quantity and quality of immunocompetent cells , various endogenous and exogenous factors that lead to this